Subdividing the commons: distributional conflict in the transition from collective to individual property rights in Kenya's Maasailand - Mwangi, Esther (Elsevier, 2007)
This paper suggests that explanations of property rights transformation need to move beyond models of relative price change and state enforcement to include accounts that accommodate conflict and competition among actors, and the possibility that state actors may not provide the enforcement that is often taken for granted. The transition from collective to individualized holdings in Kenya’s Maasailand is burdened with politics and procedural problems that can undermine the gains anticipated in that move. Moreover, in semi-arid ecological settings, individualization results in unstable land holdings, necessitating re-contracting, and reaggregation by individual parcel owners.